Activity of flavonoids on spores of the mycorrhizal fungus Gigaspora gigantea in vitro - Romero, Amalia Gisela Fersula; Siqueira, José Oswaldo (Pesquisa Agropecuaria Brasileira, 1996)
In addition to their effects on plant growth and developmental processes, plant flavonoids are active molecules in a variety of plant-microorganism relationships. In rhizobium-legume symbiosis, they act as signal molecules inducing transcription of symbiotic genes, which are essential for nodulation. In spite of the stimulating activity of certain plant flavonoids on mycorrhizal fungi, their effects on these fungi are still not well understood. In this study, conducted at the Federal University of Lavras-UFLA-, in Lavras, MG, Brazil, the effects of seven synthetic flavonoids on germination and growth of the arbuscular mycorrhizal fungus Gigaspora gigantea were evaluated. Flavonoids were dissolved in methanol and incorporated into 1% agar medium, at concentrations of 1, 2, 4 and 8 µM. All flavonoids tested were shown to be active on at least one of the parameters assessed. Spore germination was enhanced by formorionetin and hesperetin at 2 µM, whereas it was inhibited by the former at 8 µM. The number of germs tube per spore was reduced by biochanin A, quercetin and naringenin at low concentrations. Mycelial growth was stimulated by apigenin and hesperetin at 1 µM and inhibeted by biochanin A. Germ tube branching was enhanced by naringenin and formononetin at 2 µM and inhibited by morin at the same concentration. It is concluded that plant flavonoids exhibit differenciated effects on spores of the symbiotrophic fungus G. gigantea.
Keywords: soil fungi; plant metabolites; plant-microorganisms relationships; mycorrhizae; molecular signals